Study of microstructure and mechanical properties and residual stresses of 24CrNiMo steel prepared by selective laser melting and laser melting deposition - Yongsheng Zhao; Ying Wu; Dengwen Hu; Yuhua Cai; Yan Liu; Hui Chen (Journal of Materials Research and Technology, 2024)
Selective laser melting (SLM) and laser direct metal deposition (LMD) have shown promise in advanced manufacturing. However, limited research fabricating the same material using these methods, particularly regarding mechanical properties and residual stresses. In this study, 24CrNiMo blocks were prepared using SLM and LMD and subjected to stress relief annealing (SR). The microstructure, residual stresses, and mechanical properties were investigated using SEM, XRD, EBSD, mechanical testing, and μ-X360n residual stress analysis. The results showed that the microstructure of both blocks composed of α-Fe. However, due to different thermal histories, there were differences in grain size between the SLM and LMD specimens. SLM specimens exhibited higher dislocation density, resulting in increased tensile strength and yield strength, while the LMD samples had higher proportions of high-angle grain boundaries (HAGBs), providing enhanced plasticity. LMD-SR specimens exhibited stronger texture and higher content of HAGBs in the <111> direction, further improving plasticity. Both as-deposited blocks exhibited high residual stresses, ranging from 450 MPa to 580 MPa for SLM and 20 %–50 % of SLM values for LMD. After SR treatment, the strength of both specimens decreased due to a reduction in dislocation density, but the increased content of HAGBs improved plasticity. Additionally, the residual stresses in both specimens significantly decreased, transitioned from tensile stresses to compressive stresses, greatly enhancing their wear resistance. Compared to the as-deposited specimens, the SLM-SR and LMD-SR specimens exhibited a reduction in weight loss due to wear by 46.1 % and 75.2 %, respectively, indicating a significant improvement in wear resistance.